Perioperative pain management in thoracic surgery and side effects in the early postoperative period - Poniatovska, H. B.; Dubrov, S. O.; Poniatovskyi, P. L.; Sereda, S. O.; Denysiuk, M. V.; Cherniaiev, S. V.; Kotliar, A. O. (Zaporozhye Medical Journal, 2024)
Aim. To study the impact of various methods of perioperative pain management on the frequency of postoperative complications in patients with lung cancer after thoracotomy. Materials and methods. The study involved 157 patients who were divided into 4 groups. Multimodal analgesia (MA) group: according to the concept of preemptive analgesia, patients received 1000 mg paracetamol IV 1 hour before surgery and 50 mg dexketoprofen IV; in the postoperative period, dexketoprofen and paracetamol were administered every 8 hours as well as epidural analgesia: 40 mg of 2 % lidocaine solution after a catheter was placed and continuous ropivacaine infusion at a dose of 2 mg/ml (6–14 ml/h) in the postoperative period. Thoracic epidural analgesia (TEA) group: epidural analgesia: administration of 40 mg of 2 % lidocaine solution after catheter placement, continuous ropivacaine infusion in the postoperative period at a dose of 2 mg/ml (6–14 ml/h). Preemptive analgesia (PA) group: according to the concept of preemptive analgesia – 1000 mg IV paracetamol 1 hour before surgery as well as 50 mg IV dexketoprofen; in the postoperative period, dexketoprofen and paracetamol were administered every 8 hours. Control group (C): patients received 50 mg IV dexketoprofen for postoperative analgesia. If the severity of the pain syndrome was more than 50 mm according to the visual analogue scale (VAS), patients of all groups were given 10 mg IV morphine. The study involved the registration of side effects in the postoperative period. Results. Among 157 patients, complications in the postoperative period were observed in 61 patients (38.85 %). The frequency of complications in MA group was 10.8 % of the total number of patients, in TEA group – 12.7 %, PA – 6.4 %, and in C group – 8.9 %. The most common complaint among TEA group patients was injection-site itching (13.5 %). PA group patients had a significantly lower number of complications compared to TEA group (p = 0.035). There was no statistically significant difference in the frequency of nausea or urinary retention in patients of all groups (p > 0.05). No difference was noted in the number of pulmonary complications depending on the method of perioperative analgesia (p > 0.05). 31 patients (75.6 %) of PA group did not have any complications, that was significantly different from TEA (p = 0.021) and MA (p = 0.039) patient groups. Conclusions. The use of paracetamol and dexketoprofen combination in the perioperative period allows to reduce (p = 0.035) the total number of postoperative anesthetic complications compared to the use of only thoracic epidural analgesia. The use of a multimodal approach combining epidural analgesia and administration of paracetamol and dexketoprofen does not reduce (p > 0.05) the overall frequency of complications compared to patients without epidural analgesia.